“Entonces te quedas así como que...” Syntactic-pragmatic analysis of the particle “como” in a Caracas speaker - Aguilar Durán, Leonardo Andrés (2020)
This article reports the results of a brief research experience that aimed to explore the syntactic-pragmatic functions of the particle like in the oral and informal lan- guage of a teenage woman from Caracas. Until now, the integral analysis of the par- ticle object of attention had only been made in the formal and written variety of the Spanish of Venezuela. It was a descriptive linguistic study of a synchronic nature. The informant was a 17-year-old female teenager, with high school completed, that be- longed to the middle class. The uses of like with approximative sense have predominated, in its most typical form and as part of the functions of citation, attenuation, hypothetical comparison and discourse planning. The presentation of results is followed by the theo- retical discussion of the uses found and by some considerations regarding the sufficiency of the categories reported in the literature. If what matters is the elaboration of a clas- sification to characterize the behavior of like in Venezuelan speech, future investigations would have to expand and segment the sample.